(untitled) (International Journal of Engineering and Computer Science, 2017)
During this investigation coconut coir fibre along with banana fibre being natural fibre components, have been chemically treated with alkaline solution. Here chemically treated are mixed separately with polyester, and epoxy resins, and by using hand lay-up technique these reinforced composite materials are moulded. Several specimens have been fabricated in constant volume percentage of coir and banana fibres and by using two different resins (polyester and epoxy polymers) in order to get more accurate results.